Effects Of Post-Deposition Annealing In Oxygen Ambient Of Rf Magnetron Sputtered Ga2O3 Thin Film - Hedei, Puteri Haslinda Megat Abdul; Hassan, Zainuriah; Hock, Jin Quah (2020)
In this work, the gallium oxide (Ga2O3) thin films were deposited on silicon substrate using radio frequency (RF) magnetron sputtering and these Ga2O3 thin films were subjected to post-deposition annealing in oxygen ambient at different temperatures of 400, 600, 800, and 1000℃ for 60 minutes. The structural properties of post-deposition annealed Ga2O3 thin films were characterized using grazing incidence X-ray diffraction (GIXRD). Atomic force microscopy (AFM) and field emission scanning electron microscopy (FESEM) were employed to attain the three-dimensional surface topographies and morphologies, respectively, for the investigated Ga2O3 thin films. In additional, elemental composition of these thin films were characterized using energy-dispersive X-ray spectroscopy and thickness of the investigated Ga2O3 thin films were estimated based on the cross-sectional FESEM images. Current-voltage characteristics of the Ga2O3 thin films subjected to different postdepositional annealing temperatures were also presented in this work.